THE TIMELESS APPEAL OF SUNGUDI SAREE: PRESERVING TRADITION - Kirthika, C.S.; Sadhna; Kumar, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Indian weaving possesses an intrinsic value that extends beyond mere monetary gain and profitability. It serves as a vital connection to the past, preserving cultural significance and ensuring its endurance for future generations. This study aims to safeguard the traditional expertise imparted by the weavers in Indian villages, with a specific focus on documenting the Sungudi Srees of Thoonganagaram, a captivating city in Tamil Nadu, India. By exploring and contemplating cultural phenomena, it aims to address the challenges associated with cultural erosion and harness the intellectual potential of the weavers. Collected comprehensive data on saree production, an ethnographic research approach accompanied by visual documentation was employed. The ultimate objectives of this endeavor are to enhance the income generated from these products, sustain the valuable skills involved, and safeguard traditional weaving knowledge.